Applied of Resource Based View (RBV) theory by assessing resource heterogeneity in relation to the biomass supply chain in Malaysia - S, Salmi.; A.W.A, W.Prima.; Z, Aizat Syafiq.; H, Norlena.; A.A, Nuraini.; M.Y, Nora Yusma. (Elite Scientific Forum, 2024)
Applied the Resource Based View (RBV) theory to the biomass supply chain in Malaysia involves analyzing the unique resources and capabilities within the context of the supply chain. Focus in assessing resource heterogeneity in relation to the biomass supply chain in Malaysia involves understanding the diversity and variability of biomass resources available across different regions or sources within the country. This study aims to identify the unique characteristics, strengths, and limitations of various biomass feedstocks, which can influence supply chain dynamics, technological choices, and strategic decision-making. The qualitative measure was conducted to find the potential criteria for assessing resource heterogeneity of biomass supply chain in Malaysia. Results show that biomass type, feedstock characteristics, sustainability aspects, technology compatibility, and logistics play crucial roles in assessing the comprehensive biomass supply chain. By conducting a systematic assessment of resource heterogeneity, stakeholders can gain valuable insights into the diversity and complexity of biomass feedstock availability and characteristics in Malaysia. This information can inform strategic decision-making, technology selection, supply chain optimization, and sustainability planning in the biomass sector.